Moss-inhabiting diatom communities from Ile Amsterdam (TAAF, southern Indian Ocean) - Barbora Chattová; Marc Lebouvier; Vít Syrovátka; Bart Van de Vijver (Plant Ecology and Evolution, 2021)
Background and aims – Despite the ongoing taxonomical revision of the entire (sub)-Antarctic diatom flora, our knowledge on the ecology and community associations of moss-inhabiting diatoms is still rather limited. In the present study, our research aim was to survey the diversity together with the environmental factors structuring the epiphytic moss diatom communities on Ile Amsterdam (TAAF), a small volcanic island in the southern Indian Ocean.Material and methods – A morphology-based dataset and (physico)chemical measurements were used for the ecological and biogeographical analysis of moss-inhabiting diatom flora from Ile Amsterdam. In total, 148 moss samples were examined using light microscopy.Key results – The analysis revealed the presence of 125 diatom taxa belonging to 38 genera. The uniqueness of the Ile Amsterdam diatom flora is mainly reflected by the species composition of the dominant genera Pinnularia, Nitzschia, Humidophila, and Luticola, with a large number of unknown and often new species. This highly specific diatom flora, together with differences in the habitats sampled and the isolated position of the island, resulted in very low similarity values between Ile Amsterdam and the other islands of the Southern Ocean. From a biogeographical point of view, 40% of the taxa have a typical cosmopolitan distribution, whereas 22% of all observed species can be considered endemic to Ile Amsterdam, with another 17% species showing a restricted sub-Antarctic distribution. The NMDS analysis, based on a cluster dendrogram, divides the samples into six main groups. For each group, indicator species were determined. Both environmental data and diatom distributions indicate that apart from elevation, specific conductance, pH, and moisture are the major factors determining the structure of moss-inhabiting diatom communities on Ile Amsterdam.Conclusion – The isolated geographic position and unique climatological and geological features of the island shaped the presence of a unique diatom flora, characterised by many endemic species. The results of the study are of prime importance for further (palaeo-)ecological and biogeographical research.